Physico-chemical properties of macadamia nut shell post-gasification residues and potential agricultural application - Vu, Linh Ngoc; Nguyen, Thu Phuong; Le, Phuong Thu; Dinh, Thi Mai Thanh; Nguyen, Hong Nam (Vietnam Journal of Science and Technology, 2024)
In–depth information about the characteristics and potential use of post-gasification residues is the key to unlock the sustainability potential of biomass gasification. This study aimed to explicate the physico-chemical properties of residues after the gasification of macadamia nut shell using a commercial gasifier. The results revealed an important amount of carbon content remained in the residues, marking the low conversion efficiency of the process. The obtained residues were deemed unsuitable for use as adsorbents due to low surface areas with non-porous structures. However, the surface of the residues contained multiple carboxyl and hydroxyl functional groups. Also, a remarkable amount of K (up to 86 wt% of the char’s total inorganic elements) was observed to be evenly distributed on the char surface. The results solidified the possibility of utilizing the residues as bio-fertilizers, and provided essential data for the development of sustainable energy production processes using macadamia nut shell for gasification.